Sperm-egg fusion: a molecular enigma of mammalian reproduction - Klinovska, Karolina; Sebkova, Natasa; Dvorakova-Hortova, Katerina (International journal of molecular sciences, 2014)
The mechanism of gamete fusion remains largely unknown on a molecular level despite its indisputable significance. Only a few of the molecules required for membrane interaction are known, among them IZUMO1, which is present on sperm, tetraspanin CD9, which is present on the egg, and the newly found oolema protein named Juno. A concept of a large multiprotein complex on both membranes forming fusion machinery has recently emerged. The Juno and IZUMO1, up to present, is the only known extracellular receptor pair in the process of fertilization, thus, facilitating the essential binding of gametes. However, neither IZUMO1 nor Juno appears to be the fusogenic protein. At the same time, the tetraspanin is expected to play a role in organizing the egg membrane order and to interact laterally with other factors. This review summarizes, to present, the known molecules involved in the process of sperm-egg fusion. The complexity and expected redundancy of the involved factors makes the process an intricate and still poorly understood mechanism, which is difficult to comprehend in its full distinction.
Keywords: Ovum; ovum; Male; Integrins; Fertilization; membránové proteiny; integriny; Membrane Proteins; Spermatozoa; mužské pohlaví; receptory buněčného povrchu; imunoglobuliny; proteiny semenné plazmy; tetraspaniny; Seminal Plasma Proteins; Animals; lidé; Humans; zvířata; spermie; Receptors, Cell Surface; Tetraspanins; Immunoglobulins; fertilizace